Web-Based Food Ordering Information System at Naonaru’s Kitchen - Astriyani, Erna; Rahmani, Aulia; Elvina, Amanda; Noviantika, Fauziah (Journal Collabits, 2025)
Naonaru's Kitchen is one of the restaurants that provides a variety of foods such as fried rice, food made from seafood, burgers, pizza and various types of drinks. The current order management system is still running manually starting from recording orders from customers using order paper then handed over the order paper to the kitchen and every day the cashier must recap proof of payment one by one to make income reports. The current running system is considered less effective and can slow down the operational activities of restaurants every day, besides that the current running system causes problems, namely if the condition of the restaurant is crowded then the waiter often forgets which order comes first, order notes are often stacked in the hands of the cashier due to lack of time to the kitchen to inform of incoming orders,  Sometimes the cashier loses the order note when the customer is about to make a payment and takes time to make an income report because the cashier must recap the proof of payment one by one. This research produces a food & beverage ordering information system that helps cashiers in managing food and beverage orders so that they can provide value of menu order effectiveness for customers. This research uses Pieces for Analysis methods, diagram design using UML applications and coding using PHP programming language and MySQL databases, System development using RAD and system testing using blackbox testing.